Identification of groundwater potential zones using geoinformatics for Nagpur region - M., PRIYAMVADA; PATIL, PRAVIN (Journal of Soil and Water Conservation, 2026)
Water, a vital natural resource and essential component for all living organisms, exists in two primary forms: surface water and groundwater. Groundwater, a significant global resource, is unevenly distributed worldwide. Enhancing groundwater recharge is a fundamental hydrological parameter for assessing, managing, and modelling groundwater resources. However, determining recharge rates is a complex and challenging task, despite its crucial role in recharge assessments. The current study has been conducted in Nagpur region. The groundwater potential of the Nagpur region was assessed using remote sensing and GIS by bringing together several thematic maps. The study covers an area of about 195.57 km², which includes small water bodies (4.12 km²) and narrow valleys (0.38 km²). The land elevation across the region varies from roughly 217 m to 331 m above mean sea level. Four main geological formations are present, with Deccan Trap being the most widespread, covering nearly 44% of the area, followed by Granite Gneiss, the Lameta Group, and Alluvium. Most of the landscape is characterized by pediplain terrain, accounting for about 37% of the area, and gravelly sand soils are commonly found. The region is largely gentle in nature, with almost half of the area having a very mild slope of 0–3%. Agricultural land occupies around 16% of the total area. The analysis shows that more than half of the region falls under a moderate groundwater recharge potential. Based on these observations, the study highlights practical water-conservation measures. It recommends nala bunding along first-order streams to reduce soil erosion and runoff, and the construction of check dams on second- and third-order streams to store water and improve groundwater recharge.